TRANSLATIONS OF ENGLISH METAPHORS DESCRIBING HUMAN BEHAVIOR - Кадамбоева Мухайё Равшанбек кизи (Web of Journals Publishing, 2025)
The article is devoted to the translation of English metaphors describing human behavior, as well as the analysis of their meaning. English metaphors serve as a powerful means of expressing complex emotions and social interactions, which makes their translation a difficult but important task. Special attention is paid to the context, since the literal translation of such expressions often does not convey their true meaning. which contributes to a deeper understanding of the cultural and lexical features of the English language. The analysis helps to expand the understanding of intercultural communication and identify analogies with metaphors in other languages.
Keywords: Metaphor, human behavior, similarity, transference, emotions.